Pengaruh Sistem Pengendalian Internal dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan: Studi Empiris pada SKPD Pemerintah Kabupaten Solok Selatan - Salsabila, Hanifa; Sari, Vita Fitria (Jurnal Eksplorasi Akuntansi, 2025)
Financial reports are a crucial tool for holding local governments accountable to the public for their financial performance. The purpose of this study was to examine how human resource (HR) competency and the internal control system affect the caliber of financial reports. This research is categorized as quantitative in nature. Primary data are included in the data set. The 23 OPDs that make up the South Solok Regency area's Regional Work Units (SKPD) constitute the study's population. Sampling determination uses purposive sampling as its technique. The sample in this study was obtained from 115 respondents through a questionnaire. The research data analysis technique consists of classical assumption testing, namely normality, multicollinearity, heteroscedasticity tests. Next, a simple linear regression analysis and hypothesis testing were carried out using the SPSS program. The research findings show that the internal control system and human resources have a significant impact on the quality of financial reports